Developing a novel transitional care model for older emergency department patients and exploring the target population in Taiwan - Hung-Lin Hsu; Chung-Han Ho; Chung-Han Ho; Ying-Jia Lin; Kang-Ting Tsai; Kang-Ting Tsai; Pei-Chi Yang; Shu-Lien Hsu; Shu-Lien Hsu; An-Chi Peng; Chien-Chin Hsu; Chien-Chin Hsu; et al. (Frontiers in Medicine)
AimTransitional care in the emergency department (ED) has the potential to improve outcomes for older patients, but the specific population benefits from it and impact in Taiwan remain unclear. Therefore, we conducted this study.MethodsAn interdisciplinary team comprising emergency physicians, dedicated transitional care nurse (TCN), nurse practitioners, nurses, geriatricians, and social workers was established at a tertiary medical center. TCN conducted screenings of ED patients (≥75 years) awaiting hospitalization to identify those in need of social or care support and aid as required. The team held regular meetings to address transitional care challenges. A retrospective analysis was conducted, comparing patients who received transitional care with those who did not, between February 1, 2022, and October 31, 2022, followed by a three-month outcome assessment.ResultsWe successfully implemented a novel ED transitional care model, involving 183 patients with TCN assistance and 374 patients without. Compared to patients without TCN, those with TCN were older, had more underlying comorbidities, required more nasogastric feeding and Foley indwelling, and had higher rates of hospice and palliative care. The common needs for TCN included providing home care instructions to a foreign caregiver (38.4%), long-term care referral (30.0%), care instructions for family members of older adults in long-term care facilities (26.3%), social worker referral (3.2%), and home healthcare referral (2.1%). Follow-up analysis showed no significant outcome differences between the two cohorts.ConclusionThe model we implemented identified the population benefiting from this service. Despite the frailty of patients receiving TCN, their outcomes were not inferior, suggesting the potential benefits of TCN for this population. Further research is warranted.